Sylvanus Morgan’s Library: Books for an Aspirational Heraldic Painter - Hughes, Frances Rothwell (Library, 2021)
Abstract This article analyses an unpublished manuscript in Cambridge University Library belonging to the arms-painter and author Sylvanus Morgan (1620–1693), which contains two iterations of a library list, one beginning in 1646 and the other in 1653. The notebook also features drafts for Morgan's subsequent publications, indicating the intersection between his reading and writing habits. His library is usually only discussed in relation to that of Robert Boyle, because the remains of both men's libraries were inextricably muddled together in a joint book auction after Morgan's death. Here, the Painter-Stainer's book collection is considered in its own right, showing his (unsuccessful) attempts to elevate the status of heraldic knowledge through reference to contemporary colour theory, astronomy and philosophy. An annotated transcription of Morgan's 1653 list of printed books is included in an appendix.